Challenges in Arabic Language Learning at the Madrasah Aliyah Level - Muhamad Hasyim; Muhammad Malikurrifqi; Siti atiqatun Mulaikha; Ziadatul Khairi; Nur Ahmad; Sri Wahyuni; Tomi Adrian; Siti Zuliatin; Zikri Saputra (Journal of Scientific Studies and Multidisciplinary Research, 2026)
Students’ understanding of Islamic knowledge and developing their linguistic competence. However, in practice, Arabic language learning still faces various problems that affect the effectiveness of achieving learning objectives. This study aimed to examine the problems of Arabic language. Education at the Madrasah Aliyah level, identify the factors influencing these problems, and describe the efforts made to overcome them. The study employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation involving Arabic language teachers and Madrasah Aliyah students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicated that the problems of Arabic language education at Madrasah Aliyah encompassed both linguistic and non-linguistic aspects. Linguistic problems included difficulties in vocabulary mastery, understanding grammatical rules (nahwu and sharaf), and speaking skills. Meanwhile, non-linguistic problems involved low student learning motivation, limited learning media, differences in students’ educational backgrounds, and instructional strategies that had not been optimally implemented. Teachers’ efforts to address these problems included providing additional exercises, repeating materials, and applying more varied teaching methods. This study concludes that the problems of Arabic language education at the Madrasah Aliyah level are multidimensional and require comprehensive and contextual learning approaches to improve the quality of Arabic language instruction.